Who's who in classical mythology - Grant, Michael, 1914-2004.; Hazel, John. (New York : Routledge, 2002)
Contains more than 1,200 alphabetized entries on the major and minor figures in Greek and Roman mythology, and includes family trees, maps, and brief biographical sketches of ancient Greek and Latin writers.
Originally published: London : Weidenfeld & Nicolson, 1973.
Adult.
Adult
Keywords: Mythology, Classical -- Dictionaries; Classical mythology -- Dictionaries